PKM Digital Marketing dan Diversifikasi Ikan Bandeng Tanpa Tulang Menjadi Sambal Ikan Untuk Meningkatkan Perekonomian BUMDesa Ana Ogie Kabupaten Pangkep - Pahrul Pahrul; Sahade Sahade; Mahmuddin Mahmuddin; Khaerun Nisa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This Community Empowerment Partnership (PKM) study aims to improve the economy of BUMDesa Ana Ogie in Kanaungan Village, Pangkep Regency, which is an area with abundant milkfish production. The main problems faced by partners are (1) limited knowledge of product diversification, (2) lack of packaging skills, (3) minimal understanding of digital marketing, (4) and lack of understanding of business management. This PKM program focuses on training in processing boneless milkfish into fish sauce and optimizing digital marketing. The methods used include training in product diversification, assistance with branding and packaging, and optimization of marketing through digital platforms such as social media and marketplaces. A total of 20 participants, consisting of BUMDesa administrators and local community members, were involved in the three-day activity. The results of this program show a significant improvement in the skills of BUMDesa managers, with products that have a longer shelf life. Product marketing has also expanded, with a 45% increase in sales in three months through online platforms. The program's outputs include boneless milkfish sambal products, activity videos (https://youtu.be/PuRYrP_PDlU?si=SjzVVbERWQIWRRs8), publications in online media (https://www.beritasatu.com/network/beritasulsel/633969/dosen-unm-memberikan-pelatihandiversifikasi-produk-sambal-ikan-bandeng-tanpa-tulang-dan-pemasaran-digital), and the PakMas community service journal (Sinta 4) (https://journal.yp3a.org/index.php/pakmas/about), as well as a community service poster. This product innovation not only increases the income of BUMDesa, but also empowers women and strengthens local economic resilience.